Reference Path Generation and Obstacle Avoidance for Autonomous Vehicles Based on Waypoints, Dubins Curves and Virtual Force Field Method - Gokhan Bayar (International Journal of Applied Methods in Electronics and Computers, 2017)
In this study, reference path generation based on waypoints, Dubins curves and obstacle avoidance are focused. The motion of a wheeled robot vehicle is modeled by following the principles of point mass approach. While motion planning is performed, the importance of obtaining the shortest distance between two target points is illustrated. Dubins curves and waypoints are used to construct an optimum path generation strategy. Path planning algorithm developed is combined with an obstacle avoidance approach, known as the virtual force field method. The whole system was tested for different scenarios. In the first scenario, the path generation was tested for the case where obstacles, start and finish points of the reference path, and initial and final robot vehicle orientations were defined. In this case, waypoints were not specified. In the second scenario, the performance of the algorithm was tested for generating a complete reference path. Waypoints were specified and the shortest path between the start and end points of the desired path was generated. Successful results were obtained and presented in this paper.